Diffusion Covid-19 in polluted regions: Main role of wind energy for sustainable and health - Uçkaç, Bekir Cihan; Coccia, Mario; Kargi, Bilal (International Journal of Membrane Science and Technology, 2023)
The COVID-19 pandemic, caused by the coronavirus disease 2019, is rapidly spreading worldwide, resulting in a significant number of deaths. This ongoing environmental and sustainability discussion has raised novel and relatively unexplored questions. One of these questions pertains to the impact of heavily polluting industrial processes and less environmentally friendly production methods on the spread of COVID-19 infections. This study aims to elucidate the connection between air pollution, particulate emissions, wind conditions, energy production, and the dissemination of COVID-19 infections. The primary focus of the statistical analysis is on Italy, a country that has seen a rapid surge in confirmed cases and fatalities. The findings of this study can be summarized as follows: 1) Cities located in regions with high wind speeds and significant wind energy production in megawatts (MW) tend to have fewer COVID-19 infections. 2) Conversely, cities situated in hinterland areas, especially those adjoining large urban conglomerates, characterized by heavy industrialization, low wind speeds, and less environmentally friendly production methods, tend to have a higher number of COVID-19 cases and total fatalities. These results suggest that addressing the current COVID-19 pandemic and preparing for future epidemics similar to COVID-19 requires more than just advancements in medical and microbiological research and practices. It also necessitates a proactive approach focused on sustainable development. In conclusion, this study underscores the importance of incorporating sustainability science into strategies aimed at preventing future epidemics like COVID-19. Such an approach involves promoting renewable energy sources and cleaner production methods to reduce pollution from industrialization, ultimately influencing the factors that contribute to the transmission of coronavirus diseases and other infections within society.